Association of In-School and Electronic Bullying with Suicidality and Feelings of Hopelessness among Adolescents in the United States - Tran H. Nguyen; Gulzar Shah; Maham Muzamil; Osaremhen Ikhile; Elizabeth Ayangunna; Ravneet Kaur (MDPI AG, 2023)
Background: Suicide-related behaviors increasingly contribute to behavioral health crises in the United States (U.S.) and worldwide. The problem was worsened during the COVID-19 pandemic, especially for youth and young adults. Existing research suggests suicide-related behaviors are a consequence of bullying, while hopelessness is a more distal consequence. This study examines the association of in-school and electronic bullying with suicide-related behavior and feelings of despair among adolescents, adjusted for sociodemographic characteristics, abuse experience, risk-taking behaviors, and physical appearance/lifestyles. Method: Using Chi-square, logistic regression, and multinomial logistic regression, we analyzed the US 2019 Youth Risk Behavior Surveillance System (YRBSS) national component. The YRBSS includes federal, state, territorial, and freely associated state, tribal government, and local school-based surveys of representative sample middle and high school students in the US. The 2019 YRBSS participants comprised 13,605 students aged 12 to 18 years and roughly equal proportions of males and females (50.63% and 49.37%, respectively). Results: We observed a significant association (p < 0.05) between being bullied and depressive symptoms, and the association was more vital for youth bullied at school and electronically. Being bullied either at school or electronically was associated with suicidality, with a stronger association for youth who experienced being bullied in both settings. Conclusion: Our findings shed light on assessing early signs of depression to prevent the formation of suicidality among bullied youth.